UPAYA MEMBANGUN KELUARGA BAHAGIAN PADA MASYARAKAT DESA TUKDANA KEBUPATEN INDRAMAYU - Rasji; Kurnia, Ida; R. Rahaditya (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Tarumanagara, 2024)
The people of Tukdana Village in Indramayu Regency have chosen the relationship of a man and a woman through marriage to become a family. A family consists of a husband and wife and can have children. Although there are still those who fail to maintain the integrity of their family, the people of Tukdana Village have tried to build a happy family. How are the efforts of the people of Tukdana Village in building a happy family? The TNI problem has been carried out by searching for data through empirical methods with technical interviews with community members during the implementation of community service. Based on the results of qualitative analysis, it is known that the people of Tukdana Village have created and implemented a happy family development program, through a movement to postpone the minimum age of marriage to 19 years, appealing to teenagers to finish school up to high school level, implementing an internship program for high school graduates, seeking the economic capacity of the community through opportunities to work as migrant workers abroad, conducting family development for young married couples, utilizing community service programs by lecturers and students to foster family couples to build eternal and happy families ABSTRAK Masyarakat Desa Tukdana di Kabupaten Indramayu telah memilih hubungan seorang pria dan wanita melalui perkawinan menjadi sebuah keluarga. Keluarga terdiri atas suami dan istri serta dapat anak-anak keturunannya. Meskipun masih ada yang gagal mempertahankan keutuhan keluarganya, namun masyarakat Desa Tukdana telah berusaha membangun keluarga bahagia. Bagaimana upaya masyarakat Desa Tukdana dalam membangun keluarga yang bahagia? Permasalahan tni telah dilakukan pencaian data melalui metode empirin dengan teknis wawancara terhadap warga masyararakat pada saat pelaksanaan pengabdian kepada masyarakat. Berdasarkan hasil analisis kualitatif diketahui masyarakat Desa Tukdana telah membuat dan melaksanakan program pembangunan keluarga bahagia, melalui gerakan penundaan usia perkawinan minimal 19 tahun, menghimbau anak-anak remaja agar menyelesaikan sekolah sampai dengan tingkat sekolah menengah atas, menerapkan program magang kerja bagi anak-anak lulusan sekolah menengah atas, mengupayakan kemampuan ekonomi masyarakat melalui peluang bekerja sebagai buruh migran ke luar negeri, melakukan pembinaan keluarga pasangan perkawinan muda, memanfaatkan program pengabdian kepada masyarakat oleh dosen dan mahasiswa untuk membina pasangan keluarga agar membangun keluarga kekal dan bahagia.